Comparative morphometric and morphological study of the pollen of Beta trigyna, B. vulgaris and B. vulgaris subsp. maritima (Chenopodiaceae/Amaranthaceae sensu APG IV) - Tsymbalyuk, Zoya M.; Ivanova, Daniella; Nitsenko, Lyudmila M. (Hacquetia, 2024)
Pollen morphology of Beta trigyna, B. vulgaris and B. vulgaris subsp. maritima, last of those studied for the first time, was investigated using light and scanning electron microscopy, based on 10 herbarium specimens. The aim of the study was to provide detailed data on the pollen characteristics of these taxa to identify similarities and differences between them. Pollen grains are pantoporate, spheroidal, circular in outline; small- and medium-sized. Exine sculpture is nanoechinate, tectum is psilate or psilate-perforate. Pore membranes are nanoechinate. Diagnostic relevance of the characters of pollen grains is discussed (pollen and pore diameters, distance between pores and between pore centres, nanoechini size and density, number of nanoechini on pore membranes, structure of columellae). UPGMA dendrograms based on palynological data support the differentiation of B. trigyna (section Corollinae), B. vulgaris and B. vulgaris subsp. maritima (section Beta). The obtained characteristics of pollen grains of Beta species can be used in spore-pollen analysis, especially in identifying the impact of human economic activity in the past.